Siltstone from Southern Patagonia: its source and archaeological artifact distribution in Santa Cruz Province, Argentina - Belardi, Juan Bautista (2015)
Hunter-gatherer mobility and spheres of interaction are important characteristics worthy of investigation in Patagonian archaeology. One way to approach these is by studying the distribution of lithic archaeological materials. Siltstone (limolite) artifacts are found along the western strip of southwestern Patagonia, Argentina. Based on geomorphological studies and the high density of archaeological material, a source was located along the western margin of Cardiel Lake. Neutron activation analysis of samples from the source and archaeological sites in several neighboring basins allowed us to model its circulation. Siltstone's archaeological distribution indicates that its regional circulation had a southerly direction dating from the early Holocene. This southern vector shows an important difference when compared to the distribution of obsidian from Pampa del Asador, which has a broader circulation pattern. This could be related to a greater availability of high-quality lithic materials north of the siltstone source. This work also contributes to the construction of a lithic source database for southern Patagonia.